2007
DOI: 10.1590/s1678-77572007000200007
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of temporomandibular disorder and occlusion in treated class III malocclusion patients

Abstract: Objective:The aims of this study were to compare the prevalence of temporomandibular disorders (TMD) in individuals submitted to either orthodontic or ortho-surgical Class III malocclusion treatment and to assess the influence of occlusal aspects on TMD severity.Material and methods:The sample consisted of 50 individuals divided into two groups, according to the type of treatment (orthodontic or orthodontic with orthognathic surgery). The presence of signs and symptoms of TMD was evaluated by an anamnestic que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
2
7
0
4
Order By: Relevance
“…Another study applied motion analysis and produced similar results with restoration of mandibular movement and function but with some changes in TMJ kinematics [48]. Other studies also support the opinion that correct sagittal spit osteotomy without intraoperative fixation of the condylar position does not change the condylar position significantly and does not lead to TMD [12,19,22,37,56].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Another study applied motion analysis and produced similar results with restoration of mandibular movement and function but with some changes in TMJ kinematics [48]. Other studies also support the opinion that correct sagittal spit osteotomy without intraoperative fixation of the condylar position does not change the condylar position significantly and does not lead to TMD [12,19,22,37,56].…”
Section: Discussionmentioning
confidence: 72%
“…Eine Untersuchung mittels Bewegungsanalyse zeigte zwar postoperativ keine Veränderungen von Unterkieferbewegung und -funktion aber geringe Veränderungen in der Kinematik des Kiefergelenks [48]. Einige andere Studien konnten ebenfalls nachweisen, dass korrekt durchgeführte sagittale Osteotomien des Unterkiefers ohne Gelenkfixation keine signifikanten Verän-derungen der Kondylenposition und keine Kiefergelenkbeschwerden nach sich zogen [12,19,22,37,56].…”
Section: Discussionunclassified
“…Fang et al [27] suggested that combined orthodontic and orthognathic surgical treatment can be used safely to correct skeletal class III malocclusion without causing additional TMJ symptoms. Moreover, patients with Class III malocclusion treated with a combined orthodontic and orthognathic surgical approach do not show any differences in post-operative TMDs when compared to those treated with orthodontics alone [28]. Wolford et al [29] suggested that in Class III malocclusion patients with mandibular condylar hyperplasia, orthognathic surgery combined with high condylectomies and articular disc repositioning, provides stable and predictable outcomes without compromising jaw function.…”
Section: Discussionmentioning
confidence: 99%
“…Ni posle višegodišnjih istraživanja, uloga okluzalnih faktora u razvoju disfunkcije TMZ nije konačno definisana. Mnogobrojne studije potvrđuju ulogu okluzalnih faktora u razvoju KMD, istovremeno naglašavajući da njihov uticaj nije od primarnog značaja [15][16][17][18] , ali postoje studije koje negiraju ulogu i značaj okluzije na razvoj KMD 19 . Uprkos brojnim kontroverzama, danas preovladava stav da okluzalni faktori nemaju primarnu ulogu u etiologiji KMD-a, ali sasvim izvesno, makar delimično, participiraju i mogu da dovedu do egzacerbacije simptoma ovih oboljenja kod individua kod kojih su KMD nastale kao posledica traume, kongenitalnih poremećaja, sistemskih oboljenja ili emocionalnog stresa, čija se uloga u nastanku ovih oboljenja sve više naglašava poslednjih godina [20][21][22] .…”
Section: Diskusijaunclassified
“…Even after several years of research, the role of occlusal factors in the development of TMJ dysfunction has not been defined yet. Numerous studies confirmed the role of occlusal factors in the development of CMD, while stressing that their impact is not of primary significance [15][16][17][18] . Also, there are studies that deny the role and importance of occlusion in development of CMD 19 .…”
Section: Discusionmentioning
confidence: 99%